EVALUASI PROGRAM PENDIDIKAN DAN PELATIHAN PEGAWAI DINAS PERHUBUNGAN KABUPATEN MINAHASA SELATAN - CLAUDIA, VAANESSA; TAMPI, GUSTAAF BUDDY; LONDA, VERY (Sam Ratulangi University, 2019)
The purpose of this study was to determine the results of the evaluationof the South Minahasa District Office of Transportation Staff after participatingin an education and technical training program. There are still many obstaclesthat do not match the results of the evaluation. Utilization of facilities at the timeof the implementation of the education and training program both fromparticipants, namely the employees of the Transportation Department of SouthMinahasa Regency and from the organizers themselves have not been maximized.In this study, the authors used a qualitative approach with the type of descriptiveresearch. In this study primary data were obtained by interview and observationmethods while secondary data using literature and documentation researchmethods. The results of this study indicate that the education and trainingprogram has not fully met the target in presenting good changes in employees forthe progress of the South Minahasa District Transportation Office. This can beseen based on the results of the evaluation after following the education andtraining program based on the focus of education research and trainingregarding the four evaluation indicators as stated by Daniel Stufflebeam.Researchers provide advice on this research that is paying more attention to eachemployee placement along with the type of education and training programsparticipated by each employee in order to create professional and goodperformance in accordance with the demands of each field of staff of the SouthMinahasa District Transportation Department.Keywords: Evaluation, Education, Training Programs.